The Application of the Internet of Things in the Information Arena of the Islamic Republic of Iran Army - Ali Farahmandnezhad; Sepehr MohammadZahraee; soheil Mohammad zahraei (علوم و فنون نظامی)
Objective: The aim of this research is to explore the application of the Internet of Things (IoT) in the information sector of the Islamic Republic of Iran Army. Due to the exploratory and descriptive nature of the research questions, the formulation of hypotheses was avoided. Methodology: The research is applied in nature, and the method employed is descriptive with a mixed approach. The data collection methods include fieldwork, library research, interviews, questionnaires, documents, websites, and note-taking. The study population consisted of 100 personnel from the Islamic Republic of Iran Army, ranging from second lieutenant to higher ranks, with bachelor's degrees or higher in fields related to the topic, such as telecommunications, electronics, computer science (specializing in IoT), and intelligence (specializing in information gathering). Cronbach's alpha was used to confirm the reliability of the questionnaire. Findings: After collecting the questionnaires, the statistical results obtained from the data were analyzed using SPSS software. To enhance scientific validity, the Friedman test was used for prioritization. Conclusion: The final results indicate that the Internet of Things in the information sector of the Islamic Republic of Iran Army is applied in the following components, in order of importance: information collection, processing, storage, and dissemination, along with the indicators outlined in the research.